2017
DOI: 10.1021/acs.biochem.6b01099
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Heme Degradation: ChuY Is an Anaerobilin Reductase That Exhibits Kinetic Cooperativity

Abstract: Heme catabolism is an important biochemical process that many bacterial pathogens utilize to acquire iron. However, tetrapyrrole catabolites can be reactive and often require further processing for transport out of the cell or conversion to another useful cofactor. In previous work, we presented in vitro evidence of an anaerobic heme degradation pathway in Escherichia coli O157:H7. Consistent with reactions that have been reported for other radical S-adenosyl-l-methionine methyltransferases, ChuW transfers a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 38 publications
7
29
0
Order By: Relevance
“…HutZ Ep shares moderate homology (50% identity) with E. coli ChuY. However, multiple conserved amino acids in ChuY and its homologues did not appear in HutZ Ep , including some important residues buried within the ChuY dimer interface [42], such as Glu94, Gln126, Thr132, Ser136, and Thr140 (Additional file 1). Furthermore, the spatial structure of HutZ Ep is also different from that of ChuY (Additional file 1); for example, seven α-helices exist in HutZ Ep , but only six α-helices exist in ChuY [20].…”
Section: Resultsmentioning
confidence: 99%
“…HutZ Ep shares moderate homology (50% identity) with E. coli ChuY. However, multiple conserved amino acids in ChuY and its homologues did not appear in HutZ Ep , including some important residues buried within the ChuY dimer interface [42], such as Glu94, Gln126, Thr132, Ser136, and Thr140 (Additional file 1). Furthermore, the spatial structure of HutZ Ep is also different from that of ChuY (Additional file 1); for example, seven α-helices exist in HutZ Ep , but only six α-helices exist in ChuY [20].…”
Section: Resultsmentioning
confidence: 99%
“…At least one additional electron is required to complete the reaction scheme and produce the proposed tetrapyrrole structure that is consistent with the available mass spectroscopy data. 33,36 Initially, our hypothesis was that the iron atom of heme could facilitate additional electron transfer steps or even serve as the source of one electron because under physiological conditions the heme would most likely be in the ferrous state. However, given the catalytic precedent that has been set by several other RS enzymes it is also possible that the mechanism of ring opening is independent of any metal ion.…”
Section: Proposed Reaction Mechanism For Chuwmentioning
confidence: 99%
“…Hence, in a role analogous to biliverdin reductase, it has been shown that ChuY catalyzes the NADPH-dependent reduction of anaerobilin. 36 The parallels to heme oxygenase and biliverdin reductase function are striking and suggest that accumulation of anaerobilin may be toxic to the pathogen. Consistent with this hypothesis, deletion of ChuY from the enterohemorrhagic E. coli CFT073 has been shown to result in a decrease in infectivity of the pathogen.…”
mentioning
confidence: 99%
“…This breakdown also prevents haem toxicity [21]. Under anaerobic conditions, this role is taken up by the SAMmethyltransferase ChuW and the anaerobilin reductase ChuY [22,23].The haem uptake operon is part of a larger regulatory network that allows EHEC to achieve iron homeostasis. Transcription of chuA is controlled by the iron-dependent transcriptional repressor Fur.…”
mentioning
confidence: 99%
“…This breakdown also prevents haem toxicity [21]. Under anaerobic conditions, this role is taken up by the SAMmethyltransferase ChuW and the anaerobilin reductase ChuY [22,23].…”
mentioning
confidence: 99%